Determinants of Phishing Risk Awareness among Thai University Academic Staff - Jarupunphol, Pita; Sudjarid, Wichidtra; Buathong, Wipawan (The Journal of Behavioral Science, 2024)
Background/problem: Phishing involves deceiving individuals into disclosing sensitive information. It poses a significant threat to academic institutions, impacting their security, financial stability, reputation, and operational efficiency. Objective/purpose: This research examined phishing risk awareness among academic staff at two Thai universities and investigated the factors influencing phishing threat awareness using the technology acceptance model (TAM). Design and Methodology: The study’s sample comprised 400 participants, evenly distributed with 200 individuals selected from each of two universities, each employing approximately 450 academic staff members. Data were collected using an online questionnaire. Results: The results demonstrated correlations between perceived ease of use (PEOU) and perceived usefulness (PU) (ꞵ = .52, p < .001), PEOU and attitude towards using (ATT) (ꞵ = .25, p < .001), PU and ATT (ꞵ = .57, p < .001), and ATT and phishing observation behavior (USE) (ꞵ = .14, p = .01). The relationship between phishing observation behavior (USE) and phishing risk awareness (PHA) was found insignificant (ꞵ = -.09, p = .20). However, the influences of perceived risk (PR) on USE (ꞵ = .15, p < .001) and PHA (ꞵ = .17, p < .001) were more pronounced. Conclusion and Implications: This indicates that the awareness of phishing threats is more linked to the individual’s risk perception rather than direct observation of phishing incidents. This suggests that enhancing phishing risk awareness should focus on educating individuals about the risks of phishing rather than increasing the visibility of phishing attempts.